Addressing Peer-to-Peer Resident Mistreatment Through the Use of Forum Theatre: A Pilot Intervention. (1st June 2022) - Botros-Brey, Sylvia; Dyurich, Adriana; Pfeiffer, Alixandria; Prestigiacomo, Roberto; Wang, Hanzhang; Page-Ramsey, Sarah M.; Basler, Joseph W.; Berggren, Ruth
Abstract : Problem: Residents may experience mistreatment by faculty, peers, nurses, or patients. While faculty are reportedly the primary contributors to mistreatment, residents can also be offenders, which merits study. Forum theatre (FT) is an experiential learning modality requiring a peer group to develop problem-solving strategies. FT was piloted to address mistreatment among residents. The objective was to determine whether FT was feasible, acceptable to resident learners, and could lead to self-reported changes in perceptions or behaviors, providing program directors a focused option to address professionalism as a competency. Approach: This initiative was conducted from September 2019 through February 2021 in obstetrics–gynecology and urology residencies at UT Health San Antonio and consisted of 3 phases: a focus group to identify mistreatment experienced by residents, resident volunteers to create and act out the FT scenario, and enactment of the FT scenario during didactic time. Residents completed anonymous retrospective pre- and postsurveys, as well as at 6–8 months after, to assess knowledge, attitudes, and self-reported and observed behaviors. Wilcoxon rank-sum tests and 2-sample t tests for proportions were used to compare variables between groups. Outcomes: The FT was completed successfully in both departments during didactic time. Twenty-six residents participated, 24 (92%) responded. Most respondents (23, 96%) would recommend FT to colleagues for teaching professionalism. Behavior changes were reported by 15 (63%) participants after the program. After 6–8 months, self-reported mistreatment behaviors had decreased, including "making fun of others" (15 (63%) to 10 (38%), P = .04) and sending "disparaging texts" (13 (54%) to 7 (27%), P =.02). Next Steps: The use of FT during regularly scheduled didactic times was feasible and well received among residents. The evaluation demonstrated sustained self-reported behavior changes. Plans are ongoing to expand this approach to other medical specialties and professions institutionally.